Stereotypes and language learning motivation a study of L2 learners of Asian languages - Nikitina, Larisa (Routledge, 2020)
"This book explores stereotypes that learners of six Asian languages- Japanese, Mandarin, Korean, Myanmar, Thai and Vietnamese-hold about the target language country, its cultures and people. Some of the findings, such as the language learners' mental images of Myanmar, Thailand and Vietnam, are presented here for the first time. Recognizing that stereotypes, and attitudes embedded in them, have an impact on people's actions and behavioural intentions, this book examines whether and how the country stereotypes held by the students influenced their motivation to learn the target language. Besides providing worthwhile insights into the content and structure of the country stereotypes and their relationship with language learning motivation, this book offers methodological and theoretical advancements. Drawing on intellectual heritage of Russian psychologist Lev Vygotsky (1896-1934) the book highlights how the concepts of word meaning (znachenie slova) and word sense (smysl) could be fruitfully employed in studies on stereotypes that people learning a foreign language hold about a target language country. This book will appeal to all readers interested in stereotypes that people have about foreign countries and also to educators and researchers who study language learning motivation"--